Ungdomsbreve fra Vilhelm Beck til Jens Vahl: Danske teologer og blodskam 1680-1770 - Larsen, Kurt E. (Kirkehistoriske Samlinger, 2003)
The Danish pastor Vilhelm Beck (1829-1901) is known as the strong leader of the Inner Mission Society from 1861-1901. Letters from the years 1857-1861 from Beck to his friend and colleague Jens Vahl (1828-1898) extend our knowledge of Beck from a rather unknown period of his life as he tells Vahl about the revival in his parish and about different experiences in church life. Vahl was the leader of the Tract Society, an important person in Foreign Missions and kindly disposed towards cooperation with other churches and with other groups within the Danish Church. The letters show how Beck gradually moved in another, more sacrament-oriented and more revivalist direction that after 1861 made Inner Mission a special branch within the church.